2018
DOI: 10.1371/journal.pone.0205205
|View full text |Cite
|
Sign up to set email alerts
|

Development and biological evaluation of Ti6Al7Nb scaffold implants coated with gentamycin-saturated bacterial cellulose biomaterial

Abstract: Herein we present an innovative method of coating the surface of Titanium-Aluminium-Niobium bone scaffold implants with bacterial cellulose (BC) polymer saturated with antibiotic. Customized Ti6Al7Nb scaffolds manufactured using Selective Laser Melting were immersed in a suspension of Komagataeibacter xylinus bacteria which displays an ability to produce a 3-dimensional structure of bio-cellulose polymer. The process of complete implant coating with BC took on average 7 days. Subsequently, the BC matrix was cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…Gentamycin is also a widely used drug in the treatment of bone infection, and it is a substance designed for use in bone recovery. Dydak et al [143] reported that gentamycin-modified BC showed very low cytotoxicity and was able to inhibit the proliferation of the bone pathogen, S. aureus. This modification strategy allows us to meet the demands of implantology and has high suitability for orthopedic applications.…”
Section: Applications Of Fuctionalized Bcmentioning
confidence: 99%
“…Gentamycin is also a widely used drug in the treatment of bone infection, and it is a substance designed for use in bone recovery. Dydak et al [143] reported that gentamycin-modified BC showed very low cytotoxicity and was able to inhibit the proliferation of the bone pathogen, S. aureus. This modification strategy allows us to meet the demands of implantology and has high suitability for orthopedic applications.…”
Section: Applications Of Fuctionalized Bcmentioning
confidence: 99%
“…Moreover, BC’s chemical composition is identical with composition of plant cellulose and is not digested in harsh environment of stomach [ 30 ]. Our team has already shown the suitability of BC chemisorbed with antibiotics and antiseptics to fight against biofilms formed by pathogens responsible for infections of wounds [ 31 ], bones [ 32 , 33 , 34 ], and oral cavity [ 35 ]. Therefore, the purpose of the present study was to determine the usability of BC chemisorbed with 3-BP and SER to act against biofilm of H. pylori .…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria can not only aggregate on the implant surface, forming a biofilm and resisting antibacterial treatment, but also impede osseointegration and form alveolar absorption [21]. In order to enhance the antibacterial properties of biomaterials, various modification strategies have been applied, such as the loading of antibiotics, cross-linking of drugs, and construction of micro-nano topography [12,22,23]. Although antibacterial properties have improved, few methods with a focus on improving both osteogenesis and antibacterial properties have been reported.…”
Section: Introductionmentioning
confidence: 99%